2021
DOI: 10.1177/1747493021995271
|View full text |Cite
|
Sign up to set email alerts
|

Pre-stroke physical activity and admission stroke severity: A systematic review

Abstract: Background Admission stroke severity is an important clinical predictor of stroke outcomes. Pre-stroke physical activity (PA) contributes to stroke prevention and may also be associated with reduced stroke severity. Summarising the evidence to-date will inform strategies to reduce burden after stroke. Aims To summarise the published evidence for the relationship between pre-stroke physical activity (PA) and admission stroke severity and to provide recommendations for future research. Summary of Review MED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…26 A recent systematic study in 2021 showed that pre-stroke physical exercise may be associated with reduction in admission stroke severity. 27 The study showed that pre-stroke exercise was associated with reduction in infarct size, reduced risk factors for stroke and distal occlusion. 27 In 2020, Damsbo et al 28 showed that pre-stroke exercise was associated with better cognitive performance at 1 and 6 months after stroke.…”
Section: Physical Exercise Reduces the Severity Of Stroke Injury And Improves Functional Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…26 A recent systematic study in 2021 showed that pre-stroke physical exercise may be associated with reduction in admission stroke severity. 27 The study showed that pre-stroke exercise was associated with reduction in infarct size, reduced risk factors for stroke and distal occlusion. 27 In 2020, Damsbo et al 28 showed that pre-stroke exercise was associated with better cognitive performance at 1 and 6 months after stroke.…”
Section: Physical Exercise Reduces the Severity Of Stroke Injury And Improves Functional Outcomesmentioning
confidence: 99%
“…27 The study showed that pre-stroke exercise was associated with reduction in infarct size, reduced risk factors for stroke and distal occlusion. 27 In 2020, Damsbo et al 28 showed that pre-stroke exercise was associated with better cognitive performance at 1 and 6 months after stroke. In 2018, Reinholdsson et al 29 showed that light exercise like walking 4 hours/week or moderate exercise of 2 to 3 hours/ week, both were associated with less severe stroke and better functional outcomes as indicated by lower NIHSS scores.…”
Section: Physical Exercise Reduces the Severity Of Stroke Injury And Improves Functional Outcomesmentioning
confidence: 99%
“…Measuring pre-stroke physical activity is challenging with inherent limitations based on study design ( 103 , 129 ). Based on a recent systematic review we conducted, along with other studies measuring pre-stroke physical activity ( 23 , 130 132 ), most studies were retrospective and case-control designs and relied on self-reported physical activity questionnaires to recall pre-stroke activities ( 17 , 18 ). Questionnaires are relatively inexpensive, low resource burden, convenient to administer, and ideal for clinical settings ( 102 ).…”
Section: Measuring Pre-stroke Physical Activity Levelsmentioning
confidence: 99%
“…As such, few prospective cohort studies have been conducted, including the Physician's Health Study ( 132 ) and Women's Health Initiative cohorts ( 23 ), but neither studies included objective measures of physical activity. Nevertheless, self-reported questionnaires remains a feasible, cost-effective and pragmatic method to measure pre-stroke physical activity in acute or subacute settings, as demonstrated by many investigators ( 17 , 18 ).…”
Section: Measuring Pre-stroke Physical Activity Levelsmentioning
confidence: 99%
See 1 more Smart Citation